Understanding and managing the threat of disruptive events to the critical national infrastructure. Issue 3 (1st July 2014) - Fuzhan Nasiri, Dr; Thurlby, Robert; Warren, Kim
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to describe a high-level model portraying the relationships between operational, investment, commercial and regulatory pressures, and reports the early findings from testing alternative strategies, both over the long- and short-term. Concern about the vulnerability of utility networks (electricity, gas and water) and other infrastructures, including transport and telecommunications, to environmental, terrorist and other threats has increased in recent years. This has been motivated both by a perceived increase in such threats and by recognition that the commercial pressures and regulation of companies operating these infrastructures could unintentionally have increased that risk. Powerful simulation tools already help utility operators develop asset investment polices to improve both the performance and resilience of their networks, while others have helped increase their capability to respond efficiently when disruptive events occur. However, these tools need to be further developed to increase understanding of how the interdependencies between operational, investment, commercial and regulatory pressures influence and eventually define the strategic policies available to these organisations and what the long-run consequences will be for the resilience of these systems and hence for service continuity. Design/methodology/approach – Use of system dynamics methods and tools to develop a new approach to strategy and policy development for risk management for organisations operating the critical national infrastructure. Findings – System dynamics is a valid approach to address the problem of understanding risk and developing risk mitigation and management strategies for organisations operating the critical national infrastructure. To develop policies that will effectively manage and mitigate risk in the critical national infrastructure, it is essential to identify and model the interactions and interdependencies between the organisational, investment, commercial and regulatory factors. Research limitations/implications – The research has developed a proof-of-concept model and set of simulation tools which produce good results using test data from one type of organisation operating in the critical national infrastructure. The model has not been tested using data from other types of organisations. Similarly, the software written in the model has not been tested in operational conditions and further testing will be required. Practical implications – The model at the moment can only be applied to single organisation. The interactions between organisations are not in scope. Originality/value – Although some work in the field using simulation tools and methods has been done in the USA, the use of system dynamics and its application to the specific situation on the UK and Europe is new. The model uses earlier work which applied system dynamics to the subject of asset investment planning, but is a major step forward from this work. Risk and resilience is one of the major challenges facing operators of the critical national structure. This work will be of potential value to all these organisations.